Analysis of Drug Resistance in Children Receiving Antiretroviral Therapy for Treatment of HIV-1 Infection in Uganda - Towler, William I.; Barlow-Mosha, Linda; Church, Jessica D.; Bagenda, Danstan; Ajuna, Patrick; Mubiru, Micheal; Musoke, Philippa; Eshleman, Susan H. (AIDS research and human retroviruses, 2010)
We analyzed drug resistance in HIV-infected Ugandan children who received antiretroviral therapy in a prospective, observational study (2004–2006); some children had prior single-dose nevirapine (sdNVP) exposure. Children received stavudine (d4T), lamivudine (3TC), and nevirapine (NVP); treatment was continued if they were clinically and immunologically stable. Samples with >1,000 copies=ml HIV RNA were analyzed by using the ViroSeq HIV Genotyping System (ViroSeq). Subtype A and D pretreatment samples also were analyzed with the LigAmp assay (for K103N, Y181C, and G190A). ViroSeq results were obtained for 74 pretreatment samples (35 from sdNVP-exposed children (median age, 19 months) and 39 from sdNVP-unexposed children (median age, 84 months). This included 39 subtype A, 22 subtype D, 1 subtype C, and 12 inter-subtype recombinant samples. One sample had nonnucleoside reverse transcriptase inhibitor (NNRTI) resistance, one had nucleoside reverse transcriptase inhibitor (NRTI) resistance, and three had protease inhibitor (PI) resistance. Y181C was detected by using LigAmp in five pretreatment samples [four (14.8%) of 37 samples from sdNVP-exposed children, one (4.2%) of 24 samples from children without prior sdNVP exposure; p¼0.35]. Among children who were not virally suppressed at 48 weeks of treatment, all 12 tested had NNRTI resistance, as well as resistance to 3TC and emtricitibine (FTC); three had resistance to other NRTIs. Seven of those children had a ViroSeq result at 96 weeks of treatment; four of the seven acquired resistance to additional NRTIs by 96 weeks. In Uganda, clinically and immunologically stable children receiving nonsuppressive antiretroviral treatment regimens are at risk for development of drug resistance.
Keywords: Drug Resistance; Children; Antiretroviral Therapy; Treatment of HIV; Infection